2019
DOI: 10.1002/anie.201903740
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylation of C−N Bonds in Tertiary Amines Catalyzed by Low‐Valent Iron Catalysts

Abstract: The first iron catalysts able to promote the formal insertion of CO into the C−N bond of amines are reported. Using low‐valent iron complexes, including K2[Fe(CO)4], amides are formed from aromatic and aliphatic amines, in the presence of an iodoalkane promoter. Inorganic Lewis acids, such as AlCl3 and Nd(OTf)3, have a positive influence on the catalytic activity of the iron salts, enabling the carbonylation at a low pressure of CO (6 to 8 bars).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The absence of H 2 circumvented the dehalogenation of the arylbromide in this palladium‐catalyzed reaction. Interestingly, the possibility of generating high pressures of CO (up to 26 bars, allowed iron‐catalyzed carbonylation of the N−CH 3 bond in N,N‐dimethylaniline in 73 % yield under 9 bars of CO, using a double autoclave system (see Scheme and the Supporting Information) . While chemical looping is common strategy in the realm of heterogenous catalysis, the present work hence exemplifies how liquid chemical looping can unlock thermodynamically unfavored transformations, at low temperatures, without the need for sophisticated metal catalysts.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…The absence of H 2 circumvented the dehalogenation of the arylbromide in this palladium‐catalyzed reaction. Interestingly, the possibility of generating high pressures of CO (up to 26 bars, allowed iron‐catalyzed carbonylation of the N−CH 3 bond in N,N‐dimethylaniline in 73 % yield under 9 bars of CO, using a double autoclave system (see Scheme and the Supporting Information) . While chemical looping is common strategy in the realm of heterogenous catalysis, the present work hence exemplifies how liquid chemical looping can unlock thermodynamically unfavored transformations, at low temperatures, without the need for sophisticated metal catalysts.…”
Section: Methodsmentioning
confidence: 77%
“…Interestingly,t he possibility of generating high pressures of CO (up to 26 bars,allowed iron-catalyzed carbonylation of the NÀCH 3 bond in N,Ndimethylaniline in 73 %y ield under 9bars of CO,u sing adouble autoclave system (see Scheme 5and the Supporting Information). [25] While chemical looping is common strategy in the realm of heterogenous catalysis,the present work hence exemplifies how liquid chemical looping can unlock thermodynamically unfavored transformations,atlow temperatures, without the need for sophisticated metal catalysts. [a] Reaction conditions: In atwo-chamber system surmounted with acooler,p ure MF is introducedinthe reserve chamber (A) and the catalytic chamber (B) is charged with 7 mmol catalyst (5 mg) and 1mL DMF.…”
Section: Angewandte Chemiementioning
confidence: 91%
“…Preparing amides by the carbonylation of amines directly is of great significance. Cantat et al reported the carbonylation of N , N -dimethylaniline to aromatic amide . Just like most other CO carbonylation reactions, this amine synthesis requires the use of equivalent CH 3 I at high temperature (200 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Cantat et al reported the carbonylation of N,N-dimethylaniline to aromatic amide. 39 Just like most other CO carbonylation reactions, 40−42 this amine synthesis requires the use of equivalent CH 3 I at high temperature (200 °C). Li and co-workers 43 reported a palladium-catalyzed carbonylation reaction in which qunaternary ammonium halides were employed to synthesize tertiary amides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…54 Although it is not the same transformation, Cantat recently reported the ironcatalyzed amine to amide transformation of an N,Ndimethylaniline substrate by taking advantage of the acylation of a tertiary amine followed by the extrusion of Me + as MeI. 55 Also, the participation of Fe in Curtius-like rearrangements has only a few precedents, such as the work from Xia, forming isocyanates from hydroxamates through an Fe II -nitrenoid complex. 56 In order to gain insight into the mechanism of this unprecedented reactivity, the well-defined 1 Me complex was heated under a CO atmosphere (1 bar).…”
mentioning
confidence: 99%